Pandangan Hans-Georg Gadamer Terhadap Fenomena Panik di Tengah Pandemi Covid-19: Sebuah Interpretasi - Dina Datu Paonganan; Admadi Balloara Dase (Undiksha, 2022)
This article examines the phenomenon of panic in society during the COVID-19 pandemic usingHans-Georg Gadamer's concept of understanding the process of forming new horizons. This paper contains a critical analysis using the hermeneutic method to review the panic phenomenon in the Covid-19 pandemic situation in Indonesia. The data analyzed are news and research on panic in society. The panic that occurred in society caused by the era of the covid-19 pandemic developed the post-truth phenomenon in which it no longer stated objective truth, but was based on emotions and beliefs. The author that panic is the experience of the community in understanding information related to covid-19 sees this as understanding. Therefore, the dogmatization of these changes resulted in an increasingly dramatic panic in society.